Žinių vadybos poveikis darniam vystymuisi Zenona - Atkočiūnienė, Ona (Information & Media, 2008)
Šiandieninis pasaulis sparčiai keičiasi. Vienas iš svarbiausių pokyčių, sąlygojančių vystymąsi – žinios ir žinojimas. Straipsnyje analizuojamas darnus vystymasis, kaip pagrindinės ilgalaikės visuomenės vystymosi ideologijos sąsajos su žinių vadyba. Akcentuojama, kad žinios, patirtis, kompetencija, pilietinė atsakomybė motyvuoja žmones laikytis aplinkosauginių, socialinių ir ekonominių darnaus vystymosi reikalavimų. Pastebima, kad vienas iš būdų studijuoti kognityvinę darnaus vystymosi dimensiją yra mąstymas apie vystymąsi, kaip apie socialinį mokymosi procesą, kuris individualiu lygmeniu padeda žmonėms kontroliuoti jų asmeninę darnaus vystymosi patirtį, savarankiškai ją taikyti problemų sprendimui bei savo ateities kūrimui. Organizaciniu lygmeniu, taikant žinių vadybos priemones ir būdus, darbuotojų intelektinės žinios paverčiamos organizacijos darniu konkurenciniu pranašumu. Globaliu lygmeniu – darnaus vystymosi principai taikomi kuriant darnią pasaulio visuomenę. The impact of knowledge management to the sustainable development Zenona Ona Atkočiūnienė Summary Modern society has been undergoing transformation into a new harmonious, environmentally friendly society, with the aim of providing the mankind with possibilities to create a safer, healthier and more prosperous world with continuous education and learning, new knowledge, values, attitudes and a need to know, to comprehend ant to act meaningfully and responsibly. Sustainable development requires a constant change which is determined not only by individual capabilities, but also by regulation of social and economic development and its ensuring at the state and organisational levels. Application of knowledge management to the implementation of objective of sustainable development places great emphasis on intellectual capital, creativity, innovations encouraging the sharing of experience, ensures the interaction of technologies, talents and tolerance beneficial for an organization and the whole economy, culture of life-long learning. The article analyzes sustainable development as the main, long-term interaction of the societal development ideology with knowledge management. It points out that knowledge, experience, competence, civic responsibility give reasons for compliance with environmental, social and economic requirements of sustainable development. It has been noticed that one of the ways to study a cognitive dimension of sustainable development is through contemplation about the development as a social process of learning which helps people to control an individual level their personal experience of sustainable development by independently applying it to problem solution and shaping their own future. At an organisational level, intelectual knowledge of employees are transformed into a competitive advantage of the organisation by applying the measures and methods of knowledge management.